Simulation study of mixing process in oil tank; Science and Technologies in Geology, Exploration and Mining; Vol. 17, Iss. 14 - Butov V. G. Vladimir Grigorievich; Nikulchikov A. V. Andrei Viktorovich; Nikulchikov V. K. Viktor Kensorinovich; Solonenko V. A. Viktor Aleksandrovich; Yashchuk A. A. Aleksey Aleksandrovich (2017, 2017)
The article presents the results of research on basic parameters of screw-type device designed to lift off, mix, and re-suspend sediments which build up on the bottom of the oil tank. When crude oil is stored in tanks, invariably solid particles and heavy paraffin sediments are deposited. To prevent any sediment from building up on the bottom of the storage tank and to ensure all oil requirements are met, screw-type devices or propellers which are installed at the first horizontal ring of a tank are basically used to lift off, mix, and re-suspend sediments. The rotating blades of the propeller produce collimated turbulent flow in crude oil. The collimated flow is strong enough to mix oil in the tank lifting solids off the floor. 600 rotation of the propeller shaft ensures faster blending. Correct position in the tank creates cross tank and bottom-to-top-to-bottom circular mixing action in oil. The current simulation study has revealed the dependence of sediment resuspension velocity on the distance from the rotating blades at various temperatures and corresponding oil viscosity. The conditions to re-suspend oil tank bottom sediments were defined for the given propeller geometry. It has been proved that the use of screw-type devices is an effective method to lift solids off the floor of the storage tank and ensure required characteristics of tank oil.